Adaptación de la Escala de Bienestar Social para profesores y personal escolar - Bilbao, Marian (2024)
Social well-being is the assessment of social functioning, which plays a key role in mental health. In the school context, teachers and school staff can promote students’ well-being, but it is related to their own. To assess their social well-being, the Keyes social well-being scale was adapted to the school context. Psychometric properties were analyzed in 899 teachers and school staff in Valparaíso, Chile. The results suggest that 22 items are suitable for use, showing good fit to the data. Smaller school size and school participation are associated with higher social well-being. The adapted scale can be a useful tool to measure socio-affective variables of adults in the school community.